(untitled) (The Pakistan Development Review, 2006)
During the 1950s, 1960s and most of the 1970s inequality followed declining trends in the most developed and developing countries. However, the inequality trends have been reversed in most countries since the early 1980s. First, inequality started rising in the mid- to late- 1970s in the United States, United Kingdom, Australia and the New Zealand, which were the first among the OECD countries to adopt a neoliberal policy approach. In United Kingdom the increase in inequality was quite pronounced as the Gini coefficient of the distribution of net disposable income rose more than 30 percent between 1978 and 1991, which was twice as fast as that recorded in United States for the same period. The Scandinavian countries and the Netherlands were next to follow where inequality followed a U-shaped pattern. From 1970 to 80, Finland and France also experienced a halt in declining trends in inequality. In Italy inequality rose by 4 points between 1992 and 1995. In 1993 the Gini coefficient for Japan stood at 0.44, which is approximately the same as United States and far higher than the likes of Sweden and Denmark. Most of this increase in income inequality in these industrialised countries is explained by a rise in earnings inequality [Cornia, et al. (2004)]. Since 1989, inequality in the transition countries of Central Europe has also witnessed increasing trends but they remain modest when compared to former USSR and Southeastern Europe where the Gini coefficients rose on average by 10-20 points which is 304 times faster than the Gini in Central Europe. The rise in inequality in this region has been attributed to rise in returns to education following liberalisation [Rutkowski (1999)].